1995
DOI: 10.1016/0370-2693(95)01005-b
|View full text |Cite
|
Sign up to set email alerts
|

Bose-Fermi equivalence and interacting string field theory

Abstract: The bosonic representation of the half string ghost in the full string basis is examined in full. The proof that the comma 3-vertex (matter and ghost) in the bosonic representation satisfy the Ward-like identities is established thus completing the proof of the Bose Fermi equivalence in the half string theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…They also proved BRST -invariance and showed that BRST -invariance implies both K-invariance and the W L identities. In [6], the K-invariance of the comma theory was established and the BRST -invariance was briefly discussed, but the WL identities were not addressed. Before discussing the WL identities and BRST -invariance in the comma theory one needs, first, to construct the WL operator in the comma theory.…”
Section: Wl Operator In the Fs Basismentioning
confidence: 99%
See 4 more Smart Citations
“…They also proved BRST -invariance and showed that BRST -invariance implies both K-invariance and the W L identities. In [6], the K-invariance of the comma theory was established and the BRST -invariance was briefly discussed, but the WL identities were not addressed. Before discussing the WL identities and BRST -invariance in the comma theory one needs, first, to construct the WL operator in the comma theory.…”
Section: Wl Operator In the Fs Basismentioning
confidence: 99%
“…1 in [3]), it is not obvious that all ingredients of the comma theory employing the comma bosonic fields ϕ L (σ) and ϕ R (σ) are equivalent to those constructed using the original comma fermi fields c L (σ), c R (σ), b L (σ) and b R (σ) appearing in [5]. It has been claimed in [6], that the ghost bosonic vertices in the comma operator formulation obey the same overlap equations as the fermionic vertices and are identical. However a rigorous proof was not presented in [5].…”
Section: Wl Identities In the Comma Basismentioning
confidence: 99%
See 3 more Smart Citations